Budaya Organisasi Berorientasi Hasil dan Komitmen Organisasi Sebagai Pemoderasi Pengaruh Partisipasi Penganggaran Pada Senjangan Anggaran - Widyasari, Putu Indah; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2018)
A budget is used by management to communicate plans, allocate resources, and coordinate operational activities and corporate strategies. Employee participation in budgeting and performance assessment based on budgets can lead to dysfunctional behavior by performing the budgetary slack. This study aims to empirically test the capability of organizational culture of results oriented and organizational commitment to moderate the influence of budgetary participation on budgetary slack. The study was conducted at 3.4 and 5 star hotels located in Denpasar. Respondents are Head of Department who is involved in the process of preparing and implementing the budget, amounting to 84 respondent. The analysis technique used is regression analysis of moderation. The results show that organizational culture that is result oriented and organizational commitment moderate the influence of budgetary participation on budgetary slack. The higher budgeting participation causes less budgetary slack when there is a high result-oriented organizational culture and organizational commitment. Keywords: Organizational culture, commitment organizational, budgetary participation, budgetary slack